Runge-Kutta method of order four for solving fuzzy delay diﬀerential equations under generalized diﬀerentiability - Indrakumar, S.; Kanagarajan, K. (Journal of Applied Nonlinear Dynamics, 2026)
This paper portrays and interpret the fuzzy delay differential equations using the generalized differentiability concept by applying the Generalized Characterization Theorem. Subsequently we also investigate the problem of finding a numerical approximation of solutions. Moreover, the Runge-Kutta approximation methods is implemented and its error analysis are also discussed. The applicability of the theoretical results are illustrated with some examples.